Method for recycling waste foamy copper and application thereof

The energy consumption during recycling of copper waste is solved by dissolving sulfur powder using a diluted desulfurization solution mixed with hydrazine hydrate and deionized water in an enzyme-free blood sugar sensor, and stirring and mixing with the surface-treated copper foam, followed by vacuum drying and ball milling. High problem, high efficiency and low energy consumption of Cu and Cu7S4 mixture preparation is achieved.

CN119410894APending Publication Date: 2025-02-11HEXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411557208.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, copper waste is recycled for enzyme-free blood sugar sensors with high energy consumption, especially in the vulcanization step.

Method used

The diluted desulfurization solution was obtained by mixing hydrazine hydrate with deionized water, and the sulfur powder was dissolved to prepare the vulcanized solution, and stirred with the surface-treated copper foamed foam, followed by vacuum drying and ball milling to obtain a mixture containing Cu and Cu7S4.

Benefits of technology

This method achieves large and rapid preparation of mixtures containing Cu and Cu7S4 at lower energy consumption, reducing vulcanization temperature and energy consumption, and improving product purity and repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410894A_ABST
    Figure CN119410894A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste foamy copper recovery, in particular to a method for recycling waste foamy copper and application of the method. The method comprises the following steps: mixing hydrazine hydrate with deionized water to obtain a diluted desulfurization solution; sulfur powder and the diluted desulfurization solution are stirred and mixed for the first time, and a sulfuration solution is obtained; cleaning the surface of the waste foamy copper to obtain surface-treated foamy copper; the vulcanization solution and the surface treatment foamy copper are stirred and mixed for the second time, then vacuum drying is conducted, and a crude product mixture containing Cu and Cu7S4 is obtained; grinding the crude product of the crude product mixture under an inert atmosphere condition to obtain a mixture; wherein the temperature of the second stirring and mixing is 15-35 DEG C, and the time of the second stirring and mixing is 5-6 minutes. According to the method, a large amount of CuxS bionic enzyme products or lithium ion battery anode products can be rapidly prepared from the mixture containing Cu and Cu7S4 under the condition of relatively low energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of waste foam copper recovery, and in particular to a method for recovering waste foam copper and an application thereof. Background Art

[0002] Since diabetes affects people's nervous system and causes many health problems, daily monitoring of blood glucose concentration is essential to prevent and avoid life-threatening complications. At present, enzyme-free blood glucose sensors are used in diabetes diagnosis due to their advantages such as high sensitivity, wide linear range, high anti-interference and stability. In enzyme-free sensors, precious metals and / or alloys, transition metals and / or metal oxides and metal sulfides can realize the electrocatalytic oxidation of glucose like enzymes. At present, copper-based materials (Cu, Cu2O, CuO, Cu x S) has the advantages of low cost, environmental friendliness, high repeatability and low overpotential, so copper-based materials can become a potential bionic enzyme for glucose sensors; in addition, copper sulfide of copper-based materials has a special layered structure and a high theoretical lithium storage capacity, and is expected to be a substitute for commercial carbon electrodes in lithium-ion battery anode products.

[0003] In addition, with the rapid development of the copper smelting industry, a large amount of copper waste will be generated. At this stage, the effective recovery and reuse of non-ferrous metal waste such as copper is particularly important. The recovered non-ferrous metal waste can create huge economic and environmental benefits. However, the current recovery of copper waste is mainly focused on the recovery of copper metal, and less on the use of copper waste in enzyme-free blood glucose sensors. Moreover, most of the copper waste used in enzyme-free blood glucose sensors requires a higher sulfidation temperature, resulting in high energy consumption in this process. Summary of the invention

[0004] The present application provides a method for recycling waste foam copper and its application to solve the following technical problem: how to reduce the energy consumption of copper waste for sulfurization in enzyme-free blood glucose sensors.

[0005] In a first aspect, the present application provides a method for recycling waste foam copper, the method comprising:

[0006] Mixing hydrazine hydrate with deionized water to obtain a diluted desulfurization solution;

[0007] The sulfur powder and the diluted desulfurization solution are first stirred and mixed to dissolve the sulfur powder in the diluted desulfurization solution to obtain a sulfidation solution;

[0008] The waste copper foam is surface cleaned to obtain the surface treated copper foam;

[0009] The sulfide solution and the surface treated copper foam are stirred and mixed for a second time, and then vacuum dried to obtain a crude mixture containing Cu and Cu7S4;

[0010] ball milling the crude mixture under an inert atmosphere to obtain a mixture containing Cu and Cu7S4;

[0011] Wherein, the temperature of the second stirring and mixing is 15° C. to 35° C., and the time of the second stirring and mixing is 5 min to 6 min.

[0012] Optionally, the weight m1 of the surface-treated copper foam and the volume V1 of the sulfide solution satisfy the relationship: m1:V1≤5:50, wherein the unit of m1 is g and the unit of V1 is mL; and / or

[0013] The volume V2 of the hydrazine hydrate and the total volume V3 of the diluted desulfurization solution satisfy the relationship: V2:V3≥4:5; and / or

[0014] The weight m2 of the sulfur powder and the total volume V3 of the diluted desulfurization solution satisfy the relationship: m2:V3≤15:50, wherein the unit of m2 is g, and the unit of V3 is mL.

[0015] Optionally, the vacuum drying temperature is 50°C to 60°C; and / or

[0016] The first stirring and mixing time is 1 h to 3 h.

[0017] Optionally, the waste copper foam is surface cleaned to obtain the surface treated copper foam, comprising the steps of:

[0018] The waste copper foam is ultrasonically cleaned in deionized water, and then ultrasonically cleaned in an acetone solution to obtain a first surface-treated copper foam;

[0019] The first surface-treated copper foam is ultrasonically cleaned in deionized water, and then ultrasonically cleaned in a dilute hydrochloric acid solution to obtain a second surface-treated copper foam;

[0020] The second surface-treated copper foam is ultrasonically cleaned in deionized water to obtain a surface-treated copper foam.

[0021] Optionally, the ball milling speed is ≥200 r / min, and the ball milling time is ≥3 h.

[0022] In a second aspect, the present application provides a mixture containing Cu and Cu7S4, wherein the mixture is prepared by the method described in the first aspect.

[0023] In a third aspect, the present application provides a sensor electrode for detecting glucose content, wherein the sensor electrode comprises the mixture described in the second aspect, the sensor electrode comprises a glassy carbon electrode and the mixture attached to the surface of the glassy carbon electrode, and the sensitivity of the sensor electrode is ≥1.7mA·L / (mmol·cm 2 ).

[0024] In a fourth aspect, the present application provides a method for preparing the sensor electrode according to the third aspect, the method comprising:

[0025] Mixing deionized water, ethanol and perfluorosulfonic acid resin to obtain a conductive mixed solution;

[0026] Dispersing the mixture described in the second aspect in the conductive mixed solution to obtain an activated slurry;

[0027] The activation slurry is coated on the surface of the glassy carbon electrode and then dried to obtain a sensor electrode.

[0028] In a fifth aspect, the present application provides a cuprous sulfide-based lithium-ion battery, wherein the cuprous sulfide-based lithium-ion battery comprises the mixture described in the second aspect.

[0029] In a sixth aspect, the present application provides a method for preparing the cuprous sulfide-based lithium-ion battery according to the fifth aspect, the method comprising:

[0030] Mixing carbon black, sodium alginate and the mixture described in the second aspect to obtain a mixed slurry;

[0031] The mixed slurry is coated on the surface of the metal substrate, and then vacuum dried to obtain an electrode sheet;

[0032] Punching and weighing the electrode sheet, and then assembling the battery under an inert atmosphere to obtain a cuprous sulfide-based lithium-ion battery;

[0033] The weight m3 of the carbon black, the weight m4 of the sodium alginate and the weight m5 of the mixture satisfy the relationship: m3:m4:m5=8:1:1.

[0034] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0035] The embodiment of the present application provides a method for recycling waste foam copper. The method uses hydrazine hydrate and deionized water as a diluted desulfurization solution, and then uses the diluted desulfurization solution to dissolve sulfur powder to obtain a sulfide solution with strong reducing properties. The sulfide solution and the surface-treated foam copper are then stirred and mixed for the second time. The temperature of the second stirring and mixing is 15°C to 35°C, and the time of the second stirring and mixing is 5min to 6min. The surface-treated foam copper can be reduced at room temperature in a short time to obtain a relatively pure crude mixture containing Cu and Cu7S4. Finally, a large amount of a mixture product containing Cu and Cu7S4 can be obtained in batches after ball milling. Therefore, the method can realize a large amount of and rapid preparation of Cu containing a mixture of Cu and Cu7S4 under low energy consumption. x S bionic enzyme cuprous sulfide product. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0038] Figure 1 A schematic flow chart of a method for recycling waste copper foam provided in an embodiment of the present application;

[0039] Figure 2 A detailed schematic diagram of a method for recycling waste foam copper provided in an embodiment of the present application;

[0040] Figure 3 A schematic flow chart of a method for preparing a sensor electrode provided in an embodiment of the present application;

[0041] Figure 4 A schematic flow chart of a method for preparing a cuprous sulfide-based lithium-ion battery provided in an embodiment of the present application;

[0042] Figure 5 A mixture Cu provided in Example 1 of the present application x X-ray diffraction results of S;

[0043] Figure 6 A mixture Cu provided in Example 1 of the present application x S Scanning electron microscopy results at different magnifications;

[0044] Figure 7 CV graphs of the voltage of the sensor electrode and different glucose concentrations provided in Example 1 of the present application;

[0045] Figure 8 This is an IT diagram of the sensor electrode provided in Example 1 of the present application in NaOH solutions with different glucose concentrations, wherein: Figure 8 (a) is a schematic diagram showing the correlation between the current signal intensity of the sensor electrode and different glucose concentrations in different time periods. Figure 8 (b) is a schematic diagram of the linear fitting of the current of the sensor electrode and different glucose concentrations;

[0046] Fig. 9 This is a schematic diagram of the lithium storage performance results of the cuprous sulfide-based lithium-ion battery provided in Example 2 of the present application under test conditions of 0.01V to 3V. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0048] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0049] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0050] Figure 1 A schematic flow chart of a method for recycling waste foam copper provided in an embodiment of the present application is exemplarily shown;

[0051] like Figure 1 As shown, the embodiment of the present application provides a method for recycling waste foam copper, the method comprising:

[0052] S1. Mixing hydrazine hydrate with deionized water to obtain a diluted desulfurization solution;

[0053] S2. The sulfur powder and the diluted desulfurization solution are first stirred and mixed so that the sulfur powder is dissolved in the diluted desulfurization solution to obtain a sulfiding solution;

[0054] S3. The waste copper foam is surface cleaned to obtain a surface treated copper foam;

[0055] S4. The sulfide solution and the surface treated copper foam are stirred and mixed for a second time, and then vacuum dried to obtain a crude mixture containing Cu and Cu7S4;

[0056] S5. The crude mixture was ball-milled under an inert atmosphere to obtain a mixture containing Cu and Cu7S4;

[0057] Wherein, the temperature of the second stirring and mixing is 15° C. to 35° C., and the time of the second stirring and mixing is 5 min to 6 min.

[0058] The second stirring and mixing time can be 15°C, 20°C, 25°C, 30°C or 35°C.

[0059] The second stirring and mixing time can be 5.0 min, 5.1 min, 5.2 min, 5.3 min, 5.4 min, 5.5 min, 5.6 min, 5.7 min, 5.8 min, 5.9 min or 6.0 min.

[0060] It should be noted that the inert atmosphere may be an argon atmosphere.

[0061] In some optional embodiments, the weight m1 of the surface-treated copper foam and the volume V1 of the sulfide solution satisfy the relationship: m1:V1≤5:50, wherein the unit of m1 is g and the unit of V1 is mL; and / or

[0062] The volume V2 of the hydrazine hydrate and the total volume V3 of the diluted desulfurization solution satisfy the relationship: V2:V3≥4:5; and / or

[0063] The weight m2 of the sulfur powder and the total volume V3 of the diluted desulfurization solution satisfy the relationship: m2:V3≤15:50, wherein the unit of m2 is g and the unit of V3 is mL;

[0064] In these embodiments, the weight m1 of the surface-treated copper foam and the volume V1 of the sulfide solution can satisfy the relationship: m1:V1≤5:50, and the sulfide solution and the surface-treated copper foam can be chemically reacted to obtain a sufficient crude mixture containing Cu and Cu7S4; in addition, the volume V2 of hydrazine hydrate and the total volume V3 of the diluted desulfurization solution can satisfy the relationship: V2:V3≥4:5, which can promote the presence of sufficient reducing hydrazine hydrate in the diluted desulfurization solution, so as to facilitate the subsequent chemical reaction between the sulfide solution and the surface-treated copper foam to obtain a sufficient crude mixture containing Cu and Cu7S4; in addition, the weight m2 of sulfur powder and the total volume V3 of the diluted desulfurization solution can satisfy the relationship: m2:V3≤15:50, which can promote the presence of sufficient sulfur powder in the diluted desulfurization solution to obtain a sufficient sulfide solution, thereby facilitating the subsequent chemical reaction between the sulfide solution and the surface-treated copper foam to obtain a sufficient crude cuprous sulfide mixture containing Cu and Cu7S4.

[0065] In some optional embodiments, the vacuum drying temperature is 50° C. to 60° C.; and / or

[0066] The first stirring and mixing time is 1h to 3h;

[0067] In these embodiments, the vacuum drying temperature can be 50°C to 60°C. Through vacuum drying, the liquid phase components in the crude cuprous sulfide can be converted into gaseous state and separated from the crude mixture containing Cu and Cu7S4, thereby obtaining a relatively pure crude mixture containing Cu and Cu7S4; in addition, the first stirring and mixing time can be 1h to 3h, and the sulfur powder and the diluted desulfurization solution can be fully mixed through the first stirring and mixing to obtain a sulfide solution with better reducing property.

[0068] The vacuum drying temperature may be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C.

[0069] The first stirring and mixing time can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h.

[0070] Figure 2 A detailed schematic diagram of a method for recycling waste foam copper provided in an embodiment of the present application is exemplarily shown;

[0071] In some optional embodiments, such as Figure 2 As shown, the waste copper foam is surface cleaned to obtain the surface treated copper foam, comprising the steps of:

[0072] S301. The waste copper foam is ultrasonically cleaned in deionized water, and then ultrasonically cleaned in an acetone solution to obtain a first surface-treated copper foam;

[0073] S302. The first surface-treated copper foam is ultrasonically cleaned in deionized water, and then ultrasonically cleaned in a dilute hydrochloric acid solution to obtain a second surface-treated copper foam;

[0074] S303. The second surface-treated copper foam is ultrasonically cleaned in deionized water to obtain a surface-treated copper foam;

[0075] In these embodiments, the waste copper foam is sequentially cleaned with deionized water, acetone solution, deionized water, dilute hydrochloric acid solution and deionized water by ultrasonic cleaning, which can effectively wash away impurities on the surface of the waste copper foam to obtain a relatively pure surface-treated copper foam, thereby ultimately improving the purity of the mixture containing Cu and Cu7S4 with lower energy consumption.

[0076] In some optional embodiments, the ball milling speed is ≥200 r / min, and the ball milling time is ≥3 h;

[0077] In these embodiments, the ball milling speed may be ≥200 r / min, and the ball milling time may be ≥3 h. The ball milling may facilitate the conversion of the crude mixture containing Cu and Cu7S4 into a mixture containing Cu and Cu7S4 of finer particle size.

[0078] Based on a general inventive concept, such as Figure 5 and Figure 6 As shown, an embodiment of the present application provides a mixture containing Cu and Cu7S4, and the mixture is prepared by the method.

[0079] The mixture is realized based on the above method. The specific steps of the method can refer to the above embodiment. Since the mixture adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be described one by one here.

[0080] Based on a general inventive concept, an embodiment of the present application provides a sensor electrode for detecting glucose content, wherein the sensor electrode comprises the mixture, the sensor electrode comprises a glassy carbon electrode and the mixture attached to the surface of the glassy carbon electrode, and the sensitivity of the sensor electrode is ≥1.7mA·L / (mmol·cm 2 ).

[0081] The sensor electrode is realized based on the above-mentioned mixture. The specific source of the mixture can be referred to the above-mentioned embodiment. Since the sensor electrode adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0082] It should be noted that the sensitivity of the sensor electrode can be ≥1.7mA·L / (mmol·cm 2 ), which indicates that the sensor electrode has high sensitivity and that the mixture in the sensor electrode can efficiently catalyze glucose conversion.

[0083] Figure 3 A schematic diagram of a method for preparing a sensor electrode provided in an embodiment of the present application is exemplarily shown;

[0084] like Figure 3 As shown, based on a general inventive concept, an embodiment of the present application provides a method for preparing the sensor electrode, the method comprising:

[0085] S1. Mixing deionized water, ethanol and perfluorosulfonic acid resin to obtain a conductive mixed solution;

[0086] S2. dispersing the mixture in the conductive mixed solution to obtain an activated slurry;

[0087] S3. coating the activated slurry on the surface of the glassy carbon electrode and then drying it to obtain a sensor electrode;

[0088] This method is a method for preparing the above-mentioned sensor electrode. The specific composition of the sensor electrode can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.

[0089] Based on a general inventive concept, an embodiment of the present application provides a cuprous sulfide-based lithium-ion battery, wherein the cuprous sulfide-based lithium-ion battery includes the cuprous sulfide powder.

[0090] The cuprous sulfide-based lithium-ion battery is realized based on the above mixture. The specific source of the mixture can be referred to the above embodiment. Since the cuprous sulfide-based lithium-ion battery adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be described one by one here.

[0091] Figure 4 A schematic flow chart of a method for preparing a cuprous sulfide-based lithium-ion battery provided in an embodiment of the present application is exemplarily shown;

[0092] Based on a general inventive concept, such as Figure 4 As shown, the embodiment of the present application provides a method for preparing the cuprous sulfide-based lithium-ion battery, the method comprising:

[0093] S1. mixing carbon black, sodium alginate and the mixture to obtain a mixed slurry;

[0094] S2. The mixed slurry is coated on the surface of the metal substrate, and then vacuum dried to obtain an electrode sheet;

[0095] S3. The electrode sheet is punched and weighed, and then the battery is assembled under an inert atmosphere to obtain a cuprous sulfide-based lithium-ion battery;

[0096] The weight m3 of the carbon black, the weight m4 of the sodium alginate and the weight m5 of the mixture satisfy the relationship: m3:m4:m5=8:1:1.

[0097] The method is a method for preparing the above-mentioned cuprous sulfide-based lithium-ion battery. The specific composition of the cuprous sulfide-based lithium-ion battery can refer to the above-mentioned embodiment. Since the method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0098] It should be noted that the weight m3 of the carbon black, the weight m4 of the sodium alginate and the weight m5 of the mixture can satisfy the relationship: m3:m4:m5=8:1:1, which can promote sufficient mixing between the carbon black, sodium alginate and the mixture to facilitate the subsequent uniform distribution of the mixture on the surface of the metal substrate, thereby obtaining a cuprous sulfide-based lithium-ion battery with excellent performance.

[0099] It should be noted that the metal substrate may be copper foil; and the inert atmosphere may be argon.

[0100] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions or conditions recommended by the manufacturer.

[0101] Example 1

[0102] like Figure 2 As shown, a method for recycling waste foam copper comprises:

[0103] S1. Mix 40 mL of hydrazine hydrate with 10 mL of deionized water to obtain 50 mL of diluted desulfurization solution;

[0104] S2. The first step is to mix 15 g of sulfur powder and 50 mL of a diluted desulfurization solution by stirring to dissolve the sulfur powder in the diluted desulfurization solution to obtain a sulfiding solution;

[0105] S301. 5 g of waste copper foam was ultrasonically cleaned in deionized water for 5 min, and then ultrasonically cleaned in an acetone solution for 5 min to obtain a first surface-treated copper foam;

[0106] S302. The first surface-treated copper foam is ultrasonically cleaned in deionized water for 5 min, and then ultrasonically cleaned in a 1 mol / L dilute hydrochloric acid solution for 5 min to obtain a second surface-treated copper foam;

[0107] S303. The second surface-treated copper foam is ultrasonically cleaned in deionized water for 5 min three times to obtain a surface-treated copper foam;

[0108] S4. The sulfidation solution and the surface treated copper foam are stirred for a second time, the surface treated copper foam is stirred until it turns completely black, and the sulfidation solution becomes clear after sufficient sulfidation and is immediately vacuum dried to obtain a crude mixture containing Cu and Cu7S4;

[0109] S5. The crude mixture containing Cu and Cu7S4 was ball-milled under an argon atmosphere to obtain a mixture containing Cu and Cu7S4;

[0110] The temperature of the second stirring and mixing is 15° C. to 35° C., and the time of the second stirring and mixing is 6 minutes.

[0111] The vacuum drying temperature is 50°C;

[0112] The first stirring and mixing time is 2 h.

[0113] The grinding speed is 200r / min and the grinding time is 3h.

[0114] The mixture prepared by the above method is used as a sensor electrode for detecting glucose content. The preparation steps of the sensor electrode are as follows: Figure 3 As shown, the specific process is:

[0115] S1. 665 μL of deionized water, 335 μL of ethanol and 100 μL of 5% perfluorosulfonic acid resin were mixed and ultrasonicated for 30 min to obtain a conductive mixed solution;

[0116] S2. 5 mg of the mixture was dispersed in the conductive mixed solution to obtain an activated slurry;

[0117] S3. Drop 10 μL of the activated slurry on the surface of a glassy carbon electrode with a diameter of 3 mm, and then dry it to obtain a sensor electrode.

[0118] Example 2

[0119] Based on the contents disclosed in Example 1, the following modifications are further made:

[0120] The mixture prepared in Example 1 is used as a raw material for a cuprous sulfide-based lithium-ion battery. The preparation steps of the cuprous sulfide-based lithium-ion battery are as follows: Figure 4 As shown, the specific process is:

[0121] S1. mixing carbon black, sodium alginate and the mixture to obtain a mixed slurry;

[0122] S2. The mixed slurry is coated on the surface of the metal substrate, and then vacuum dried to obtain an electrode sheet;

[0123] S3. The electrode sheet was punched (with a diameter of 12 mm) and weighed, and then the battery was assembled under argon atmosphere to obtain a cuprous sulfide-based lithium-ion battery;

[0124] Among them, the weight of carbon black m3, the weight of sodium alginate m4 and the weight of the mixture m5 satisfy the relationship: m3:m4:m5=8:1:1.

[0125] The vacuum drying is performed at 90° C. overnight.

[0126] Example 3

[0127] Based on the contents disclosed in Example 1, the following modifications are further made:

[0128] The second stirring and mixing time is 5 min.

[0129] The vacuum drying temperature was 55°C;

[0130] The first stirring and mixing time was 1 h.

[0131] Example 4

[0132] Based on the contents disclosed in Example 1, the following modifications are further made:

[0133] The second stirring and mixing time was 5.5 min.

[0134] The vacuum drying temperature is 60°C;

[0135] The first stirring and mixing time is 3 h.

[0136] Comparative Example 1

[0137] Dendritic Cu-Cu2S was deposited on a glassy carbon electrode using an in-situ electrochemical deposition method to prepare an enzyme-free glucose sensor (reference Xu G, Ge C, Liu D, Jin L, Li Y, Zhang T, Rahman M, Li X, Kim W. In-situ electrochemical deposition of dendritic Cu-Cu2S nanocomposites onto glassy carbon electrode for sensitive and non-enzymatic detection of glucose, Journal of electroanalytical Chemistry, 2019, 847, 113177).

[0138] Comparative Example 2

[0139] The CuS-Cu2S hybrid material was prepared using a hydrothermal process (hydrothermal temperature of 150°C, hydrothermal time of 10 h); the obtained CuS-Cu2S hybrid material was drop-coated on a glassy carbon electrode to obtain a CuS-Cu2S modified glassy carbon electrode (reference Huang W, Liu F, Huang Y, Yang W, Zhong H, Peng J. Facile one-pot synthesis of hollow-structured CuS / Cu2S hybrid for enhanced electrochemical determination of glucose, Electrochemistry, 2021, 89(4), 340-347).

[0140] Comparative Example 3

[0141] The core-shell CuS-Cu2S modified carbon nanotube-graphene nanocomposite was prepared by hydrothermal method (hydrothermal temperature was 150°C, hydrothermal time was 12h); the core-shell CuS-Cu2S modified carbon nanotube-graphene nanocomposite was drop-coated on a glassy carbon electrode to obtain a CuS-Cu2S modified glassy carbon electrode (reference Fu Y, Jin W. Facile synthesis of core-shell CuS-Cu2S based nanocomposite for the high-performance glucose detection, Materials Science and Engineering: C, 2019, 105, 110120)

[0142] Related experiments and effect data:

[0143] The mixture obtained in Example 1 was subjected to surface feature analysis, and the results were as follows: Figure 5 and Figure 6 As shown by Figure 5 It can be seen that the mixture Cu x The main components of S are Cu (JCPDS card: 04-0836) and Cu7S4 (JCPDS card: 23-0958); Figure 6 It can be seen that the mixture Cu x The S particles are not uniform, and some Cu x S maintains the skeleton structure of the copper foam, while the other part of the mixture Cu x Small particles of S appear on the surface of the skeleton structure of these copper foams. These factors can improve the x Sensitivity of the sensor electrode for glucose detection.

[0144] The sensor motors of Example 1 and each comparative example were counted respectively, and the specific process was as follows: the catalytic effect of the modified electrode on glucose was tested on a CHI660E electrochemical workstation using cyclic voltammetry (CV graph) and amperometric current response technology (IT curve) in a three-electrode system (cuprous sulfide modified glassy carbon electrode as working electrode, platinum electrode counter electrode, silver / silver chloride reference electrode), the electrolyte was 0.1 mol / L sodium hydroxide solution, and the test range was 5 μmol·L -1 ~3.975mmol·L -1 The results are shown in Table 1. Figure 7 and Figure 8 shown.

[0145] Table 1 Sensitivity of each sensor electrode

[0146]

[0147] Depend on Figure 7 It can be seen that after the mixture Cu x The signal of the sensor electrode modified with S to glucose increases continuously with the increase of glucose concentration. x The electrical signal intensity of the S-modified sensor electrode can be used to determine the glucose concentration; Figure 8 (a) It can be seen that when a lower glucose concentration (5 μmol / L) is added, the Cu x The current signal of the sensor electrode modified by S changes significantly, which indicates that the mixed Cu x S has a significant catalytic effect on glucose; Figure 8 (b) It can be seen that the mixture Cu x The current I of the sensor electrode modified by S and the glucose concentration C satisfy the linear relationship: I = 93.11C + 6.28. Therefore, according to the actual test results, it can be known that the mixture Cu x The sensitivity of the S-modified sensor electrode was 1.33 mA·L / (mmol·cm 2 ), and the test range of the sensor electrode is 5 μmol·L -1 ~3975μmol·L -1 .

[0148] In addition, the lithium storage performance of the cuprous sulfide-based lithium-ion battery obtained in Example 2 was tested, and the results were as follows: Fig. 9 As shown, after 160 cycles, the mixture containing Cu x The discharge capacity of the cuprous sulfide-based lithium-ion battery containing the mixed Cu x The cycling stability of cuprous sulfide-based lithium-ion batteries is good.

[0149] In summary, the present invention provides a method for recycling waste copper foam, which can realize the large-scale and rapid preparation of Cu2O3 from a mixture containing Cu and Cu7S4 at a low energy consumption. x S bionic enzyme products or lithium-ion battery anode products.

[0150] In addition, the present invention provides a sensor electrode for detecting glucose content, which contains Cu x S biomimetic enzyme copper-based materials can efficiently catalyze glucose conversion, thereby promoting the detection sensitivity of the sensor electrode to 1.33mA·L / (mmol·cm 2 ) and the detection range of the sensor electrode is 5 μmol·L -1 ~3975μmol·L -1 .

[0151] In addition, the present invention provides a cuprous sulfide-based lithium-ion battery, which contains the above-mentioned mixture Cu x S has good cycle stability, and the discharge capacity is still 370mAh / g after 160 cycles.

[0152] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.

Claims

1. A method for recycling waste foam copper, characterized in that: The method comprises: Mixing hydrazine hydrate with deionized water to obtain a diluted desulfurization solution; The sulfur powder and the diluted desulfurization solution are first stirred and mixed to dissolve the sulfur powder in the diluted desulfurization solution to obtain a sulfidation solution; The waste copper foam is surface cleaned to obtain the surface treated copper foam; The sulfide solution and the surface treated copper foam are stirred and mixed for a second time, and then vacuum dried to obtain a crude mixture containing Cu and Cu7S4; ball milling the crude mixture under an inert atmosphere to obtain a mixture containing Cu and Cu7S4; Wherein, the temperature of the second stirring and mixing is 15° C. to 35° C., and the time of the second stirring and mixing is 5 min to 6 min.

2. The method according to claim 1, characterized in that The weight m1 of the surface treated copper foam and the volume V1 of the sulfiding solution satisfy the relationship: m1:V1≤5:50, wherein the unit of m1 is g and the unit of V1 is mL; and / or The volume V2 of the hydrazine hydrate and the total volume V3 of the diluted desulfurization solution satisfy the relationship: V2:V3≥4:5; and / or The weight m2 of the sulfur powder and the total volume V3 of the diluted desulfurization solution satisfy the relationship: m2:V3≤15:50, wherein the unit of m2 is g, and the unit of V3 is mL.

3. The method according to claim 1, characterized in that The vacuum drying temperature is 50°C to 60°C; and / or The first stirring and mixing time is 1 h to 3 h.

4. The method according to claim 1, characterized in that The method of cleaning the surface of the waste copper foam to obtain the surface-treated copper foam comprises the following steps: The waste copper foam is ultrasonically cleaned in deionized water, and then ultrasonically cleaned in an acetone solution to obtain a first surface-treated copper foam; The first surface-treated copper foam is ultrasonically cleaned in deionized water, and then ultrasonically cleaned in a dilute hydrochloric acid solution to obtain a second surface-treated copper foam; The second surface-treated copper foam is ultrasonically cleaned in deionized water to obtain a surface-treated copper foam.

5. The method according to claim 1, characterized in that The rotation speed of the ball mill is ≥200r / min, and the time of the ball mill is ≥3h.

6. A mixture containing Cu and Cu7S4, characterized in that The mixture is prepared by the method according to any one of claims 1 to 7.

7. A sensor electrode for detecting glucose content, characterized in that: The sensor electrode comprises the mixture according to claim 6, the sensor electrode comprises a glassy carbon electrode and the mixture attached to the surface of the glassy carbon electrode, and the sensitivity of the sensor electrode is ≥1.7mA·L / (mmol·cm 2 ).

8. A method for preparing the sensor electrode according to claim 7, characterized in that: The method comprises: Mixing deionized water, ethanol and perfluorosulfonic acid resin to obtain a conductive mixed solution; Dispersing the mixture according to claim 6 in the conductive mixed solution to obtain an activated slurry; The activation slurry is coated on the surface of the glassy carbon electrode and then dried to obtain a sensor electrode.

9. A cuprous sulfide-based lithium-ion battery, characterized in that: The cuprous sulfide-based lithium-ion battery comprises the mixture of claim 6.

10. A method for preparing the cuprous sulfide-based lithium-ion battery according to claim 9, characterized in that: The method comprises: Mixing carbon black, sodium alginate and the mixture according to claim 6 to obtain a mixed slurry; The mixed slurry is coated on the surface of the metal substrate, and then vacuum dried to obtain an electrode sheet; Punching and weighing the electrode sheet, and then assembling the battery under an inert atmosphere to obtain a cuprous sulfide-based lithium-ion battery; The weight m3 of the carbon black, the weight m4 of the sodium alginate and the weight m5 of the mixture satisfy the relationship: m3:m4:m5=8:1:1.